Impacts of Tourism on Development of Urban Areas in Indian Cities: A Systematic Literature Review - AHIRWAR, Vivek; GUPTA, Rhitwik; KUMAR, Ashwani (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023, 2023)
The paper aims to review the impact of tourism on the development of urban areas in Indian cities. The study explores the various ways in which tourism acts as a catalyst for the development of any city in terms of sectors like the economic, social, and physical development of urban areas. In the context of India, there are many cities which are already heavily dependent on tourism activity, and they are flourishing as tourism cities. This also examines the challenges the cities face in managing tourism's growth and the impact it has on the local communities. The findings suggest that while tourism has the potential to bring significant benefits to urban areas, it also has negative effects on the environment, cultural heritage, and quality of life for residents. This paper is based on a systematic literature review and content analysis.